An Analysis of Influential Factors in the Use of Public Bicycles in Tehran - Ehsan Faghihi; Mojtaba Rafieian, (صفه)
Background and objectives: Bicycle-sharing is a relatively new idea, but concerns about its popularity, benefits, and potential harms behind it have sparked heated debate in the public and academic circles. However, there is still a gap between describing the phenomenon and evaluating its effectiveness. Therefore, a correct understanding of the decision-making processes in the adoption and use of shared bicycle systems can enable operators to plan their services in a more optimal way. The bicycle distribution system, if planned well, can play a complementary role in the existing transportation infrastructure. Due to the recent growth of bicycle sharing systems in large countries such as China, Europe, and the United States, there is a great interest in identifying factors influencing this system to encourage people using it. Therefore, one of the most important challenges in this field is the factors affecting the level of user satisfaction, and better identification and understanding of these factors can help improve the user experience and increase the use of this system. So far, many researches have been conducted on the components affecting the functional stability of the shared bicycles system, for example Si et al. in 2020 found that factors of efficiency, economic benefits, environmental awareness, and infrastructure incentives influence the willingness to use the shared bicycle system. Also, other studies in this field have found factors such as mental norms, behavioural norms, appearance quality, ease of use, flexibility, and safety to be effective on the willingness to use the shared bicycle system (X. Li et al., 2022; Shao et al., 2020; Zhou & Zhang; 2018). But this issue has not been fully investigated yet. Dockless Bicycle Sharing system (DBSS) with different brand names such as: Mobicycle, Ofo, Youbicycle, etc., and recently with Bidood brand, have been expanded in Iran. Therefore, according to the issues and needs raised, as well as the few studies that have been conducted in the field of investigating the efficiency and use of shared bicycles in Iran, especially in the metropolis of Tehran, the current research seeks to identify the factors affecting the use of the bicycle sharing system in Tehran in the field of urban planning and policy making, to provide guidance for city managers and operators of the shared bicycle system.Methods: In the current research, structural equation modelling (SEM) has been used to analyse latent variables, their relationships and test hypotheses according to the conceptual model of the research. It used the simple random sampling method and the required data was collected through a questionnaire, the items of which were mainly obtained from the review of the literature related to shared bicycles, its mechanism, and the presented conceptual model. A questionnaire was distributed both face-to-face and non-face-to-face (through virtual platforms such as Eitaa etc.). To check the validity and reliability of the measurement tool, improve the questions, format and scales, a pilot study of potential participants was conducted. Finally, 270 questionnaires were collected, and after screening the data, 248 questionnaires were approved. Descriptive analysis of collected data was done through SPSS version 26.0, such as data screening, frequencies, percentages and reliability analysis, and AMOS version 26.0 software was used for modelling, model analysis and hypothesis testing.Results and conclusion: Based on findings, the five components defined in the conceptual model, including quality and performance, distribution and parking, comfort and flexibility, safety and environment, and the usefulness of services, affect the satisfaction and use of users of the shared bicycle system. The results of the squared multiple correlations, which express the degree of explanation of the data variance by the model, showed that the five variables in question constitute 64% of the variance of the satisfaction variable (R2 = 0.64), with comfort and flexibility having the greatest impact on the satisfaction and use of the shared bicycle system. After that, quality and performance, service desirability, safety and environment, and distribution and parking have the most impact respectively. The findings indicate that the better the quality and performance, the conditions of distribution and parking, and the comfort and flexibility of the shared bicycle system, the greater the satisfaction and the amount of usage. In the same way, the more the shared bicycle system has higher safety and provides better services to users (have more safety and desirability), the more satisfaction and the amount of usage will be. The findings from the descriptive statistics showed that the quality and performance of bicycle sharing in terms of lightness and easy portability of bodies, beautiful design and lock function, the condition of distribution and parking of shared bicycles, the ease of access and parking, the number of bicycles, the method of deployment and management, the comfort and flexibility of bicycle sharing in terms of ease of movement in traffic, the freedom of action in choosing the route and ease of access to public transportation, and the safety of bicycles and cycling paths are not at acceptable levels. On the other hand the bicycle sharing system was considered acceptable by respondents in terms of environmental (low pollution and reduction of carbon consumption). The service quality of the bicycle sharing system was found not at a suitable level in terms of rental cost, reasonable deposit, application performance and QR sensitivity. In terms of the compatibility of the application (APP) with the mobile operating system and the ease of the registration process, however they were found at a relatively favourable level. The findings of the descriptive statistics from the satisfaction variable showed that the overall satisfaction of the users (tendency to reuse and recommend this system to others) is at a very low level, but if the services is improved, they will accept this green transportation system.The purpose of this study is to identify the factors affecting the use of shared bicycle systems in Tehran metropolis, to provide guidance for city managers and relevant operators in the field of planning, decision-making and policy making. The results of this research showed that 5 components: quality and performance, distribution and parking, comfort and flexibility, safety and environment, and the desirability of service influence the satisfaction and use of the shared bicycle system. Therefore, it is necessary for managers and urban planners and policymakers to take measures to improve the performance level of the five components proposed in this research, including the integration of shared bicycle system with public transportation, better management of distribution and parking of bicycles, increase safety of bicycles and improvement of servic